Enchevêtrement, Reconversion et éphémérité : production des territoires de la collecte et du recyclage des déchets à Hà Nôi - Sylvie Fanchette (EchoGéo)
The multi-use of space in the Red River Delta and the multi-activity of the population are long-standing strategies for coping with the scarcity of land and space in this densely populated region. Since the opening up of the country's economy, a complex and multifaceted process of urbanisation has been underway. The population has experienced a dual process of urbanisation, both 'from above' and 'from below'. This has taken place endogenously in the urban villages. This process has resulted in the formation of a complex territorial entanglement of different functions and social categories.In order to address this process, this article examines the informal actors involved in the management of recyclable waste, their practices and strategies for accessing urban resources and establishing themselves at the heart of a rapidly urbanising city. The study hypothesises that the effectiveness of the waste collection and recycling system in Hanoi is based on the transposition of the intensive, multi-active, territorial, village-based production system into the heart of the city.